I'm a stranger here myself : notes on returning to America after twenty years away - Bryson, Bill. (New York : Broadway Books, 1999)
After two decades in England, the author relocates to New Hampshire and assesses changes in American culture.
Keywords: Bryson, Bill -- Anecdotes; United States -- Description and travel -- Anecdotes; United States -- Social life and customs -- 1971- -- Anecdotes